Low-carbohydrate diets and prevalence, incidence, and progression of coronary artery calcium in the Multi-Ethnic Study of Atherosclerosis (MESA) - Hu, T. (Br J Nutr, 2019)
The evidence linking low-carbohydrate diets to cardiovascular disease is controversial, and results from epidemiologic studies are inconsistent. We aimed to assess the relationship between low-carbohydrate-diet (LCD) patterns and coronary artery calcium (CAC) scores from computed tomography in the MESA cohort. Our sample included 5,614 men and women free of clinical cardiovascular disease at baseline (2000–2002) who had a food frequency questionnaire, a baseline measure and ≥1 measure of CAC during follow-up. We excluded those with implausible energy intake or daily physical activity. The overall, animal-based, and plant-based LCD scores were calculated based on intakes of macronutrients. Relative risk regression and robust regression models were used to examine the cross-sectional and longitudinal relationship between LCD score quintile and CAC outcomes, after adjustment for multiple cardiovascular risk factors. The mean age of participants was 63 years. The median intakes of total carbohydrate, fat, and protein were 53.7%, 30.5%, and 15.6% energy/d, respectively. Among 2,892 participants with zero CAC scores at baseline, 264 developed positive scores during 2.4-year follow-up (11–59 months). Among those with positive scores at baseline, the median increase in CAC was 47 units over the course of follow-up. Neither the overall, nor the animal-based nor the plant-based LCD scores were associated with CAC prevalence, incidence, and progression. In conclusion, diets low in carbohydrate and high in fat and/or protein, regardless of the sources of protein and fat, were not associated with higher levels of CAC, a validated predictor of cardiovascular events, in this large multi-ethnic cohort.